Effect of Age and Sodium Alendronate on Femoral Fracture Repair: Biochemical and Biomechanical Study in Rats - Bonetto, Luana Mordask; Corso, Paola Fernanda Cotait de Lucas; Kuchar, Gabrielle Grosko; Gerber, Jennifer Tsi; Cunha, Leonardo Fernandes; Elsalanty, Mohammed; Zielak, João Cesar; Gonzaga, Carla Castiglia; Scariot, Rafaela (Frontiers in Cell and Developmental Biology, 2021)
Background: Bisphosphonates are drugs widely used to reduce bone resorption, increase bone mineral density and control age-related bone loss. Although there are studies reporting differences in bone structure between young and old adults, it is still difficult to predict changes related to bone aging. The aim of this study was to evaluate the effect of age and sodium alendronate on bone repair of femoral fractures in rats. Methods: Wistar rats (n = 40) were allocated into groups: O (control old-rats), Y (control young-rats), OA (alendronate old-rats) and YA (alendronate young-rats). All animals underwent linear fracture surgery followed by fixation. Groups OA and YA received 1 mg/kg alendronate three times a week until euthanasia. Biochemical analysis of calcium and alkaline phosphatase was done. After euthanasia, femurs were evaluated in relation to cross-section and flexural strength, with three-point bending test. Data were submitted to statistical analysis with significance level of 0.05. Results: There was no difference in calcium and alkaline phosphatase levels (p > 0.05). Young animals presented lower cross-section than older animals (p < 0.05). Only fractured side, young animals presented major flexural strength than older animals (p < 0.05). There was no difference between the animals that used or not alendronate in relation to cross-section and flexural strength (p > 0.05). When compared fractured and non-fractured femurs, major cross-section on fractured side was observed (p < 0.05). Flexural strength presented higher values in femurs on non-fractured side (p < 0.05). There was correlation of weight and cross-section (R = + 0.91) and weight with flexural strength of fractured and non-fractured side, respectively (R = - 0.97 and - 0.71). Conclusion: In short, there was no difference of calcium and alkaline phosphatase during the bone repair process. Age has influence in cross-section and flexural strength. Alendronate showed no association with these factors.